Liability of Grab Shops to Consumers in Online Buying and Selling - Wulan Darmawan, Surya Indah; Wahjuni, Edi; Whardana , Rhama Wisnu (Universitas Brawijaya, 2024)
In today’s era of globalisation, speed and convenience are prioritised in nearly all aspects of human activity. Sophisticated electronic tools and devices are designed to minimise manual effort and simplify tasks. The Internet has become an integral part of daily life, accessible to people across all levels of society, anytime and anywhere. This is particularly evident in the realm of online buying and selling. One example is Grab Toko, an e-commerce platform known for its aggressive promotions, offering discounts of up to 90% on electronic goods. Grab Toko advertises these deals through TV ads, social media, brochures and more, attracting many consumers with their enticing offers. However, after transferring money to purchase these items, many consumers found that their orders were never delivered, resulting in significant financial losses. This study aims to analyse the legal issues surrounding online transactions, particularly in cases like these. It adopts a normative juridical approach, examining relevant legal norms and reviewing literature to explore the theoretical concepts behind the legal problems discussed. The findings focus on two key areas: first, the liability of Grab Toko towards consumers in online transactions and second, the possible remedies available to consumers when faced with such issues.